Note on jus cogens and its recent development by the International Law Commission - Pimentel de Farias, Eduardo (Revista Jurídica Portucalense, 2021)
Through the hypothetical-deductive method, this work briefly analyzes the theory of jus cogens and its most recent development. There is still much debate about the nature and content of jus cogens. Notably, on its imperative, non-derogable and universal aspect. In the opinion of the best doctrine, it is only possible to find the true concept of jus cogens through the perspective of the progressive development of international law. For this reason, the International Law Commission decided to include the subject of jus cogens in its work program. Between 2016 and 2019, the Special Rapporteur presented four consecutive reports to the Commission, which adopted at first reading the text of the Draft Conclusion on Imperative Rules of General International Law (jus cogens). The inclusion of an illustrative list of jus cogens norms was the Conclusion Project's greatest contribution to the topic. More than fifty years later, there wasn´t justification for continuing to exclude this issue for fear that it would be misinterpreted.